Computer based analysis in the design process for the second year design studio Universiti Kebangsaan Malaysia (UKM) - Utaberta, Nangkula; Hassanpour, Badiossadat; Handryant, Aisyah Nur; Che Ani, Adi Irfan; Mohd Tawil, Norngainy (Fakulti Kejuruteraan dan Alam Bina, Universiti Kebangsaan Malaysia, 2012)
The emergence of technology and its entry to various fields, especially into education systems has its own pros and cons. but the important issue, here, should to acquiring the impact of this presence in order to enhance benefits and reduce drawbacks on educational systems. Digital software has opened a new era into designers and students of art and architecture. Understanding and learning the rules of this new era not only can help designers to keep up abreast to the newest knowledge and technology but also it can help novice designers to rescue from trap of this new world. Main goal of this paper is to study the impacts of using digital technology in design studios in second year architecture student in Universiti Kebangsaan Malaysia by analyzing and comparing student’s process and progress during one year.